The Breast Health Global Initiative 2018 Global Summit on Improving Breast Healthcare Through Resource‐Stratified Phased Implementation: Methods and overview - Duggan, Catherine; Dvaladze, Allison; Rositch, Anne F.; Ginsburg, Ophira; Yip, Cheng‐Har; Horton, Susan; Camacho Rodriguez, Rolando; Eniu, Alexandru; Mutebi, Miriam; Bourque, Jean‐Marc; Masood, Shahla; Unger‐Saldaña, Karla; et al. (Cancer, 2020)
Background The Breast Health Global Initiative (BHGI) established a series of resource‐stratified, evidence‐based guidelines to address breast cancer control in the context of available resources. Here, the authors describe methodologies and health system prerequisites to support the translation and implementation of these guidelines into practice. Methods In October 2018, the BHGI convened the Sixth Global Summit on Improving Breast Healthcare Through Resource‐Stratified Phased Implementation. The purpose of the summit was to define a stepwise methodology (phased implementation) for guiding the translation of resource‐appropriate breast cancer control guidelines into real‐world practice. Three expert consensus panels developed stepwise, resource‐appropriate recommendations for implementing these guidelines in low‐income and middle‐income countries as well as underserved communities in high‐income countries. Each panel focused on 1 of 3 specific aspects of breast cancer care: 1) early detection, 2) treatment, and 3) health system strengthening. Results Key findings from the summit and subsequent article preparation included the identification of phased‐implementation prerequisites that were explored during consensus debates. These core issues and concepts are key components for implementing breast health care that consider real‐world resource constraints. Communication and engagement across all levels of care is vital to any effectively operating health care system, including effective communication with ministries of health and of finance, to demonstrate needs, outcomes, and cost benefits. Conclusions Underserved communities at all economic levels require effective strategies to deploy scarce resources to ensure access to timely, effective, and affordable health care. Systematically strategic approaches translating guidelines into practice are needed to build health system capacity to meet the current and anticipated global breast cancer burden. Women in all resource settings continue to face significant obstacles to receiving timely, effective, and high‐quality breast cancer care. Based on a universal, disease‐specific patient pathway for breast cancer management, the Breast Healthcare Global Initiative Sixth Global Summit proposes phased implementation approaches to translate resource‐stratified guidelines into practice, including the identification of health system prerequisites required for effective stepwise implementation and monitoring.